About ‘Us’: Clusivity ⊔ exh - Bobaljik, Jonathan David; Sauerland, Uli (Proceedings of Sinn und Bedeutung, 2023)
This paper argues that two generalizations about person pronouns and agreement point towards a semantic account where both exhaustification and cumulative coordination can apply word-internally. Both generalizations involve reference to pluralities that include both the author and the addressee for which many languages use an inclusive first person morph distinct from exclusive first person and second person. The first generalization (originally due to Zwicky 1977, CLS Proceedings) holds that in terms of person categories, in languages that lack an inclusive/exclusive contrast the inclusive neutralizes with the first person and never the second person, despite overlapping meaning with both. The second generalization, which we argue is exemplified by Mandarin and Daur, is that in languages which mark clusivity only in some subsystems, but not others, then not only will the inclusive meaning be expressed as a first (not second) person, but where there are common forms between the (sub)systems, then it will be the exclusive, not the inclusive that expresses the general first person in environments that lack a clusivity contrast. Our account assumes only the two person features AUTHOR and PARTICIPANT, but uses exhaustivization instead of feature negation or Maximize Presuppostion and assumes that feature conjunction can be cumulative coordination. By analyzing the first person inclusive as AUTHOR cumulatively conjoined with exhaustivized PARTICIPANT, we derive the two generalizations noted.